PENGARUH HIDROTERAPI RENDAM AIR HANGAT PADA KAKI TERHADAP TEKANAN DARAH LANSIA PENDERITA HIPERTENSI - Anggraini, Ria; santosa, winanda rizki bagus (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2023)
Abstract Hypertension is a condition of increased blood pressure. Some studies suggest that patients with hypertension is increasing and becoming one cause of death in the world. A decrease in blood pressure can be done one of them with hydrotherapy soak in warm water. The purpose of this study was to determine the blood pressure before and after warm water hydrotherapy soak in patients with hypertension at UPT of Elderly Social Services in Tulungagung, This research using pre-experimental design with the design of one group pretest-posttest, the elderly population are 30 with data collection techniques using purposive sampling counted 25 respondent patients with hypertension and data retrieval tool using spigmomanometer and stethoscope with intervention warm water hydrotherapy soak to feet in a tub of warm water in 15 minutes during a one-week test analysis using Paired T test.The results showed before the warm water hydrotherapy soak systolic blood pressure an average of 152.0 mmHg and 94.0 mmHg diastolic. The results after doing the warm water hydrotherapy soak Average systolic blood pressure 137,2 mmHg and 84.4 mmHg diastolic. The test results obtained p-value 0:00